2022
DOI: 10.1016/j.fas.2021.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of hallux valgus surgery on improving health-related quality of life: A follow up study

Abstract: BackgroundHallus valgus (HV) negatively impacts health-related quality of life (HRQoL). Patient-reported outcome measures (PROMs) are increasingly used in clinical studies of the foot and ankle. We aimed to evaluate the effect of HV surgery on PROMs (i.e., pain scales, general HRQoL, and region-speci c scales) and radiological angles. Additionally, we aimed to determine whether the effect on these outcomes depends on the type of surgery (including open and percutaneous techniques) and if it is in uenced by pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 70 publications
4
9
0
Order By: Relevance
“…It consists of 16 questions with a score out of 100 for three separate domains, although the three domain scores can be summarized into a single index score [35]. Similarly to our results, other authors have also reported significant improvements in MOXFQ scores after HV surgery [30].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…It consists of 16 questions with a score out of 100 for three separate domains, although the three domain scores can be summarized into a single index score [35]. Similarly to our results, other authors have also reported significant improvements in MOXFQ scores after HV surgery [30].…”
Section: Discussionsupporting
confidence: 85%
“…The first point to be highlighted in this work is the fact that the HVA and IMA values, the variables most frequently used to quantify HV deformities, significantly improved from before the operation to the follow-up. This has also been frequently reported with the use of different surgical techniques [3,7,15,19,22,[29][30][31]. In our work, two of the parameters used to assess the sesamoid position, namely, the DFS and TMH, also significatively improved from the pre-to the postoperative assessment.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Further data continue to demonstrate short-term equivalency but not superiority for minimally invasive hallux valgus surgery compared with open techniques. Hernández-Castillejo et al 4 performed a longitudinal, prospective study on 72 patients (72 feet) who underwent open chevron, open scarf, or percutaneous Reverdin-Isham osteotomy for the correction of hallux valgus deformity. At a mean follow-up of 17.7 months, all patient-reported outcome measures, including the VAS pain score and Manchester Oxford Foot Questionnaire (MOXFQ), demonstrated significant improvement independent of the preoperative radiographic parameters and type of surgical procedure.…”
Section: Hallux Valgusmentioning
confidence: 99%